2007
DOI: 10.5694/j.1326-5377.2007.tb00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural and urban differentials in primary care management of chronic heart failure: new data from the CASE study

Abstract: Objective: To determine whether primary care management of chronic heart failure (CHF) differed between rural and urban areas in Australia. Design: A cross‐sectional survey stratified by Rural, Remote and Metropolitan Areas (RRMA) classification. The primary source of data was the Cardiac Awareness Survey and Evaluation (CASE) study. Setting: Secondary analysis of data obtained from 341 Australian general practitioners and 23 845 adults aged 60 years or more in 1998. Main outcome measures: CHF determined by cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 9 publications
4
47
2
Order By: Relevance
“…Different pharmacotherapy patterns in rural and metropolitan Canadian patients with HF have also been reported 9. We found that receipt of coronary angiography or interventions were lower in rural patients, consistent with the previous findings,10 24 although disparity in discharge medications was not examined in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Different pharmacotherapy patterns in rural and metropolitan Canadian patients with HF have also been reported 9. We found that receipt of coronary angiography or interventions were lower in rural patients, consistent with the previous findings,10 24 although disparity in discharge medications was not examined in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier research by Clark et al 24 showed a significantly higher prevalence of congestive HF in rural compared with metropolitan areas among patients aged 60 years and over. Furthermore, rates of echocardiography for diagnosis or specialist referrals and rate of prescribing ACE inhibitor drugs were consistently lower in rural compared with metropolitan areas 24.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Exploring rural–urban differences was the primary objective of 18 studies (35%) [2,27,28,30,31,35,36,39,43,44,49,51,54,59,68,69,71,73]. Seven studies reported medication adherence (the proportion of doses taken as prescribed over a specific time period) or persistence (the length of continuous treatment) [76], and 47 reported outcomes related to medication utilization.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 16 studies included patient self-report, 31 studies included data from medical records or registries, and 5 studies were conducted using administrative databases. Nineteen studies reported crude utilization or adherence outcome data only [8,28,35-37,39,40,50,51,53,54,63,64,67,68,71,73-75]. …”
Section: Resultsmentioning
confidence: 99%